Factores relacionados al abandono del dispositivo intrauterino en mujeres de instituciones prestadoras de servicios de salud de San Juan Iquitos 2021 - Castilla Tubilla, Jeanina Liseth (2024)
The objective was to determine the relationship between socioculturalobstetric factors and abandonment of the IUD in women treated at Health Services Provider Institutions San Juan Iquitos, 2021. Quantitative study, correlational and retrospective non-experimental design, sample of 87 women IUD users. The techniques were the interview and documentary analysis, the instruments were the sociocultural and obstetric factors questionnaire (Validity 90% and reliability 86%) and the IUD abandonment record sheet. The results were that 64.4% abandoned the IUD, 73.6% had a lower level of education, 64.4% had an unstable relationship, 82.8% had an independent occupation, 79.3% were Catholic and 59.8% had myths. and beliefs, 83.9% had heavy vaginal bleeding, 57.5% had a pelvic inflammatory condition, 83.9% did not have STIs, 82.8% did not rule out cervical cancer, 80.55% did not want to get pregnant and 87.4% did not have one DIU inlays. Applying the Chi square, statistical significance was determined: educational level (p = 0.000); couple union (p = 0.001); occupation (p = 0.001); religion (p = 0.05), myths and beliefs (p = 0.012); heavy vaginal bleeding (p = 0.015); pelvic inflammatory condition (p = 0.000); presence of STIs (p = 0.015); rule out cervical cancer (p = 0.010); pregnancy (p = 0.022) and DIU insertion (p = 0.049). The study concluded that there are factors related to IUD abandonment: level of education, union, occupation, religion, myths/beliefs, heavy vaginal bleeding, pelvic inflammatory disease, presence of STIs, ruling out cervical cancer, pregnancy and DIU embedding.